Analysis of the relation between computational thinking skills and various variables with the structural equation model - Durak, Hatice Yildiz; Saritepeci, Mustafa (Computers and education, 2018)
The aim of this study is to determine how much various variables explain students' computational thinking (CT) skills. Furthermore, it was aimed to produce a model that explains and predicts the relations between computational thinking skills and various variables. Study group consists of 156 students who were studying in 5–12. Class in 2015–2016 academic year in different schools in Ankara. Relational screening model was used in this research. Two different data collection instruments were used in this research. The first one is “Personal Information Form”. The second one is “Computational Thinking Skills Scale”. Structural Equation Model was used in data analysis so as to produce a model that explains and predicts the relations between computational thinking skills and various variables. According to research results, it was found that computational thinking skill was highly predicted by variables, respectively; “thinking styles, academic success in mathematic class, attitude against mathematic class”. •We investigated the relationship between the presence of several variables with computational thinking skill levels.•We have created a data model describing the relationship between the various variables and computational thinking skills.•Students' success in maths positively affects their computational thinking skill levels.•Students' ways of thinking have a positive effect on their computational thinking skill levels.